"A Slap of Love": A Way of Showing Love and Resolving Conflict Among Young People in South Kivu, Democratic Republic of Congo. Issue 23 (December 2021) - Mulumeoderhwa, Maroyi
This article draws on qualitative study to examine Congolese male and female high school students' attitudes toward intimate partner violence. A total of 56 boys and girls aged 16–20 years from two urban and two rural high schools in South Kivu province took part in focus groups, and 40 of these were subsequently interviewed individually. To the majority of male and female participants, when the man or boy beats his wife or girlfriend that means he loves her and he wants her to change. They believed that if a boy does not love her, he may let her go on making mistakes. Some male participants viewed women and girlfriend beating as a way to let her realize her inferiority. However, some female participants disagreed with these assumptions but they concomitantly accepted a "slap of love." There is a strong need to re-educating both males and females to address the problem, and particularly train men to treat women respectfully and non-violently.